Attention impairment in patients with cervical dystonia: An attention network test study - Xia, Kun; Han, Yongsheng; Zhou, Lanlan; Hu, Sheng; Rao, Rao; Shan, Shu; Hua, Lei (Frontiers in Psychology, 2022)
Objective: The purpose of this study was to investigate the attentional networks function characteristics of patients with CD. Methods: A total of 29 patients with cervical dystonia (CD) and 26 healthy controls (HC) were recruited. All subjects participated in the study underwent the Attention Network Test (ANT), which evaluated the efficiencies of three independent attention networks (alerting, orienting, and executive control), as well as reaction time (RT) and accuracy. Results: Significant differences between CD patients (9.86±27.95 ms) and HCs (33.62±23.41 ms) were observed in the alerting network (t=-3.40, P<0.05). In contrast, orienting network (t=0.26, P=0.79), executive control network (Z=-0.55, P=0.58), the total mean reaction time (t=-2.6, P=0.79) and the total accuracy rate (Z=-1.67, P=0.09) demonstrated no significant differences between two groups. Conclusions: Patients with CDs showed a significant deficit in the alerting network. However, they did not show any deficit in the orienting and executive control networks.